تأثير المستخمص المائي الوراق نبات الكبر Capparis Spiosa في حيوية الرؤيسات االولية لممشوكة الحبيبية Echinococcuss granulosis خارج الجسم الحي - العبودي, بسعاد عقرب معلة; القيسي, امجد قيس ابراهيم (Al-Nahrain Journal of Science, 2018)
This study was designed to evaluate the effect of aqueous leaf extracts of Cappais spinosa on viability of protoscolices for Echinococcus granulosus in vitro. Three concentrations 50, 100 or 200 mg/ ml were used. Results showed that viability ratio was significantly decreased to 0% after 60 min and 120 min when 200 mg/ ml (w/v) of leaf extract was applied. While the viability ratio was significantly decreased to 33.33 % after 60 min and 9.33 % after 120 min of treatment with extract. Moreover, viability ratio decreased to 21% after 120 min at concentration 50 mg/ml. Results also revealed that there was no significant difference in viability ratio at concentration 100 and 200 mg/ ml at zero time.